The Effect Of The Learning Cycle 5E Learning Model On Students' Learning Outcomes On Human Excretion System Materials At SMP Negeri 3 Pangkalan - Megawati, Megawati; Arif, Khairil (Universe, 2024)
This study aims to determine the effect of the Learning Cycle 5E model on student learning outcomes on the material of the human excretory system. This research was conducted at SMP Negeri 3 Pangkalan for the academic year 2021-2022. The method used in this study is a Quasi Experiment method, with a research design that is Non Equivalent Control Group Design. The sample of this study was class VIII.1 as the experimental class which was treated using the Learning Cycle 5E model and class VIII.2 as the control class which was treated using the Conventional model. The sampling technique used is purposive sampling technique. The instrument used in this study is a written test instrument in the form of multiple choice as many as 20 questions that have been tested for validity, reliability, difficulty index and discriminatory power using the help of Anates V4. The hypothesis test used is the Independent Sample T-test with the help of SPSS Version 26 and the value sig = 0.000 < 0.05 with the decision H0 is rejected. The results of this study indicate that the average N-Gain learning outcomes of students using the Learning Cycle 5E model are higher than the average N-Gain learning outcomes of students using the Conventional model on the human excretory system material in class VIII SMP Negeri 3 Pangkalan.